Pre-trial detention. Motion for pre-trial detention - Gaman, Teodora (Eximia, 2023)
The crime is the most serious antisocial act that entails the application of criminal law and sanctions specific to criminal law, thus occupying a special place within the field of violations of the norms of behavior established by law. The repressive action of public authorities to restore the rule of law is and must be conditional and clearly delineated, ensuring that individual freedom is protected and that no innocent person is affected. Justice has the role of deciding situations arising from the violation of laws since ancient times. For social life to be conducted in accordance with the rules, it is essential to have a competent authority that knows, interprets and applies them when they are breached. To this end, several procedural safeguards have been put in place to ensure the smooth conduct of the criminal proceedings. Pre-trial detention is the preventive procedural measure referring to the deprivation of liberty of an individual, before the final resolution of a criminal case, in order to conduct the criminal proceedings in good conditions or to prevent the defendant or suspect from absconding from criminal prosecution, trial or execution of the sentence. As it represents a significant restriction of personal liberty during criminal proceedings, pre-trial detention may only be ordered by a magistrate and the magistrate's powers shall be exercised only in accordance with the law. Pre-trial detention is also ordered only in certain circumstances, such as when there is a well-founded suspicion based on evidence that the person concerned has committed a criminal offence, or when it is established that the accused has absconded from trial or is in hiding, or when the actions of the accused give rise to a suspicion that he/she: steal, degrade, destroy or falsify material evidence; unlawfully influence co-defendants, witnesses or experts, or induce others to do so, thereby making it difficult to establish the truth.